Peran Aspek Kelembagaan Subak dalam Konteks Pengendalian Alih Fungsi Lahan (Kasus Subak Semat, Desa Tibubeneng, Kecamatan Kuta Utara, Kabupaten Badung) - NI LUH MADE KUSUMA PARAMITA DEWI; I DEWA PUTU OKA SUARDI; I DEWA GEDE RAKA SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
TheRole of Institutional Aspects of Subak in the Context of Land Conversion Control (A Case at Subak Semat, Village of Tibubeneng, Sub-District ofKuta Utara,Regency of Badung)Land conversion phenomenon that occurred in Bali is very high. The great number ofland conversion leads to reduced agricultural land in an irrigation system of Subak. Itwill affect the sustainability of Subak. Subak role in the institutional aspects must beconsidered in controlling land conversion. The purpose of this study was todetermine how the roles of the institutional aspects of water control system in thecontext of land conversion control at Subak Semat, Sub-District of Kuta Utara. Thescope of this research is the institutional role ofSubak as controller of the landconversion. The study examined three indicators, namely regulation, Subak activities,services and facilitation of Subak. The research method was a qualitative descriptivemethod.Based on the research results, judging from the three indicators of research,namely regulation, Subak activities and services and facilitation, institutional role inregulation needs to accommodate the provisions of the ban on land conversion intotraditional rules of awig awig. The role of the institutional aspects of the activities,services and facilitation has been at a good category, each categories was good with ascore 70% and 80%. The provisions of the ban on land conversion into traditionalrules of awig awigSubak is needed with a score 81,17% so that the land conversioncan be controlled. The lack of clear boundaries related to the ban on land conversionwill be the reference for the members of Subak if they want to sell their land. Inaddition, the role of activities, services and facilitation of Subak still need to beimproved to be in much better category.